PENDUGAAN PARAMETER GENETIK TANAMAN CABAI (Capsicum annuum L.) DI LAHAN GAMBUT - Cahya, Esa Budi Nur; ', Nurbaiti; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The experiment was carried out from July 2011 to January 2012 in Peatland Experimental garden, Agriculture Faculty, University of Riau, Rimbo Panjang Village, Tambang Distric Kampar Regency. The experimental design used was randomize block design which consist of 20 treatment in the 3 blocks. The data were statistically analyzed by using analysis of variance, followed by Duncan’s test New Multiple Range Test (DNMRT) at the level of 5%. The treatment consisted of 20 genotypes of chili that is genotype C2, C120, C51, C111, C105, C117, C118, C157, C159, F5110005-91-13-5, F5110005-91-13-12, F8002005-2-9-12-1, C140, C5, C18, C19, C143, F512005-5-11-1, C145 and C160. Variables measured were flowering date, dichotomus height, plant height, stem diameter, canopy width, leaf length, leaf width, harvesting date, fruit length, fruit stalk length, fruit diameter, weight per fruit and weight of fruit per plant. The results showed that characters have with the diversity coefficient is narrow criteria harvesting. Characters other than harvesting, has a coefficient of variability with broad criteria. Characters that have a high heritability value is plants higher, dichotomous height, fruit diameter, crown width, leaf width, leaf length, fruit stalk length, fruit length, fruit diameter, flowering date, weight per fruit, weight of fruit per plant. Harvesting date characters have low heritability criteria. Keyword : Chili, Genetic parameters, Heritability, peatland